Lower Health Literacy of Mania Than Depression Among Older People: A Random Survey of a Community Healthcare Service Center - Huang, Leping; Huang, Ruyan; Fei, Yue; Liu, Taosheng; Mellor, David; Xu, Weiyun; Xiong, Jinxia; Mao, Rongjie; Chen, Jun; Fang, Yiru; Wu, Zhiguo; Wang, Zuowei (Frontiers in Psychiatry, 2021)
Purpose: This study examines health literacy among older outpatients in two Community Healthcare Service Centers in Shanghai, China to facilitate the design of public education programs for the aged population on mood disorders (both depression and mania). Patients and methods: A total of 173 outpatients with a chronic physical illness, aged 60 years or more were randomly sampled. A health literacy questionnaire was used to assess participants’ awareness of depression and mania. Participants were then asked to label respectively two vignettes depicting depression and mania, and to give their recommendations as how to seek help for those in the vignettes and how mood disorders should be managed. Results: The 86.1% and 36.4% of participants had heard of depression and mania, respectively, with the most common source of information being relatives and friends. Over half of the participants attributed the possible causes of mood disorders to psychological trauma, pressure or stress in daily life, taking things too hard, and personality problems. Almost two-thirds of participants correctly labeled the depression vignette, but only 26.6% correctly labeled the mania vignette. The most common methods recommended by the participants as being helpful for the individuals portrayed in the vignettes were “traveling”, and help-seeking from a psychological therapist/counselor, a psychiatrist and a close family member or friend. Conclusion: The older individuals attending community healthcare service settings in Shanghai have good depression literacy but relatively poor mania literacy. However, most participants had a positive attitude toward psychiatric treatment for mood disorders.